The yield and growth characteristics of Thymus (Thymus daenensis L.) treated by different fertilizers and plant densities - jasemi, babak; shabani, ghobad; Chaichi, mohammad reza; Khoshkhoi, shahab; Norozi, Negin (Journal of Agricultural Sciences (Belgrade), 2019)
To study the effect of plant density and different nutritional systems (chemical, biological, and integrated) on the quantitative and qualitative performance of Thymus daenensis L. in Mahidasht Agricultural Training Center, Kermanshah/Iran, in 2017, an experiment was conducted in split plot design based on a randomized complete block with four replications. The first variable was two planting distances on row of 15 and 30 cm (main factor), and the subsidiary factor was four different nutritional systems including control (no-fertilizer), chemical (100 kg superphosphate, 100 kg potassium sulfate, 150 kg urea per ha), biological (8 tons of cattle manure/ha), and integrated (50% cattle manure + 50% chemical) fertilizers. The results showed that integrated fertilizer treatment produced the highest shoot dry weight  (789.1 kg/ha), essential oil content (178.7 μm/l) and root length (15.97 cm). The integrated fertilizer treatment along with 30 cm planting density resulted in the highest essential oil content of 197 μm/l. The results of this project suggested that integrated fertilizer and 30 cm planting interval is the optimal treatment in thymus production due to the higher chemical fertilizer efficiency and better crop quality.